2020
DOI: 10.1042/bsr20190756
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin induces epithelial-to-mesenchymal transition via bFGF/PI3K/ESRP1 signaling in pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal and chronic disease with a high rate of infection and mortality; however, its etiology and pathogenesis remain unclear. Studies have revealed that epithelial-mesenchymal transition (EMT) is a crucial cellular event in IPF. Here, we identified that the pulmonary fibrosis inducer bleomycin simultaneously increased the expression of bFGF and TGF-β1 and inhibited epithelial-specific regulatory protein (ESRP1) expression in vivo and in vitro. In addition, in vitro expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…40 Likewise, the anti-inflammatory effect of thalidomide was also found in influenza A (H1N1) virus-induced pulmonary injury in mice by reducing the secretion of pro-inflammatory cytokines. 41 In addition, bGFG is the mostly studied fibrosis-related factor, 42,43 and PQ has been reported to enhance bGFG expression and promote fibrosis in rat lungs, 44 while thalidomide has been reported to inhibit bFGF expression in rats, 45 which was partially in line with our findings. Moreover, considering the teratogenicity 9 and potential side-effects of thalidomide, specifically, rats and cells were treated with thalidomide alone, and it was found that alone administration of thalidomide did not affect the lungs and cells.…”
Section: Discussionsupporting
confidence: 88%
“…40 Likewise, the anti-inflammatory effect of thalidomide was also found in influenza A (H1N1) virus-induced pulmonary injury in mice by reducing the secretion of pro-inflammatory cytokines. 41 In addition, bGFG is the mostly studied fibrosis-related factor, 42,43 and PQ has been reported to enhance bGFG expression and promote fibrosis in rat lungs, 44 while thalidomide has been reported to inhibit bFGF expression in rats, 45 which was partially in line with our findings. Moreover, considering the teratogenicity 9 and potential side-effects of thalidomide, specifically, rats and cells were treated with thalidomide alone, and it was found that alone administration of thalidomide did not affect the lungs and cells.…”
Section: Discussionsupporting
confidence: 88%
“…Here, a well-validated model of EMT in the A549 human alveolar cell line was used to study the mechanism of pulmonary fibrosis, for which a suite of morphological, phenotypic and functional markers and outcomes have been well characterized [31][32][33]. BLM is widely used as an inducer of pulmonary fibrosis in animal models [34], and similar effects were validated in vitro experiments, and EMT characteristics were detected in BLM treated A549 cells [35,36]. Our research discovered that CXCL16 and its receptor CXCR6 were upregulated in BLM-induced EMT in the human A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cell injury is central to the pathogenesis of IPF [ 126 ], and is an early manifestation of bleomycin-induced inflammation [ 47 ]. DNA damage in bleomycin induced injury, as multiple risk factors for IPF, leads to loss of epithelial cell numbers and functions [ [126] , [127] , [128] ]. In IPF, epithelial cells show impaired surfactant protein production, E-cadherin and cytokeratin expression, along with other functional impairments.…”
Section: Discussionmentioning
confidence: 99%